2020
DOI: 10.1002/aur.2418
|View full text |Cite
|
Sign up to set email alerts
|

CIM6P/IGF‐2 Receptor Ligands Reverse Deficits in Angelman Syndrome Model Mice

Abstract: Angelman syndrome (AS), a genetic disorder that primarily affects the nervous system, is characterized by delayed development, intellectual disability, severe speech impairment, and problems with movement and balance (ataxia). Most affected children also have recurrent seizures (epilepsy). No existing therapies are capable of comprehensively treating the deficits in AS; hence, there is an urgent need to identify new treatments. Here we show that insulin‐like growth factor 2 (IGF‐2) and mannose‐6‐phosphate (M6P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 61 publications
(119 reference statements)
3
52
5
2
Order By: Relevance
“…Experiments on rodents with artificial increase of systemic or local IGF-2 concentration, that was achieved either by an injection of the recombinant protein or by ectopic gene expression, demonstrated that IGF-2 may alleviate cognitive deficits in animal models of AD [ 20 ], ASD [ 111 ], Angelman syndrome [ 247 ], Fragile X syndrome [ 101 ], as well as aging-related cognitive decline [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments on rodents with artificial increase of systemic or local IGF-2 concentration, that was achieved either by an injection of the recombinant protein or by ectopic gene expression, demonstrated that IGF-2 may alleviate cognitive deficits in animal models of AD [ 20 ], ASD [ 111 ], Angelman syndrome [ 247 ], Fragile X syndrome [ 101 ], as well as aging-related cognitive decline [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in a number of studies [ 11 , 111 ] that memory-enhancing action of IGF-2 is mediated primarily via IGF2R. Later it was demonstrated that activation of IGF2R by its another ligand, m6p, leads to similar effects [ 165 , 247 ]. Moreover, IGF2R is most likely responsible for clearance of protein aggregates in some neurodegenerative disorders [ 20 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations